YUSUF VA ZULAYHO ASARI YOZUVCHILAR TALQINIDA - Shomurodova Munisa Sherali qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
this article analyzes the interpretation of "Yusuf and Zulayho" by various writers. In the Quran, the works of Abdurahman Jami, Durbek, Thomas Mann, Nozim Hikmat, Habib sa'dulla and Ramz Bobojan are studied in a comparative way. The article uses literature analysis, comparative method and contextual analysis. The results show that each writer took a different approach to the work from the point of view of his ERA and worldview. In the conclusion, it is noted that the plot of"Yusuf and Zulayho " has not lost its relevance even in modern literature.